Is it easy to miss Bombay blood group? A case report - Gopalpuri, Navreet Singh; Kukar, Neetu; Garg, Parul; Handa, Anjali; Kaur, Simranjeet; Badlan, Ayush (International Journal of Research in Medical Sciences, 2025)
Bombay blood group is clinically significant blood group as it not compatible with other blood groups, such as A, B, AB, and especially the O type. Transfusion with any other blood group can lead to fatal hemolytic transfusion reactions. This is a case report where Bombay blood group was misdiagnosed as O blood group despite performing forward and reverse blood group on a gel card (column agglutination Technique). While performing, reverse grouping reaction with O cells was not checked as it was not present in the gel card. A simple test like blood grouping should be done with serious intention with incorporation of both forward and reverse grouping (with A, B and O cells), so that no patient receives wrong blood leading to fatal hemolysis due to transfusion.